Unintended Architectures:: Terrorism’s Role in Shaping Post-War France, the European Union, and the Muslim Presence in the West - Dooley, Kevin; Saunders, Robert (Journal of Conflict Studies)

(untitled) (The University of New Brunswick, 2007)
Abstract This article argues that the Algerian FLN (Front de libération nationale) played a major role in shaping the character of post-Second World War Europe. A sub-state terrorist organization dedicated to ending colonial domination of Algeria in the 1950s, the FLN effectively dashed France’s dreams of resuming its position as a global power, which in turn promoted greater commitment on the part of France to the nascent European Community. The FLN may also be said to have inadvertently contributed to the first large-scale immigration of Muslims into Europe during the modern era, while also severely complicating the relationship between France and its Muslims for decades. While the FLN’s use of political terror shaped national liberation movements across the developing world, the primary focus of this article will instead be on the ways in which the FLN’s victory in Algeria served to promote French participation in the European experiment and how the exodus of France’s Arab and Berber allies at the conclusion of the conflict added to the extant piedmont of Muslim Europeans reshaping the ethnography of Western Europe.